Scores and principal components: the relationship between components due to subjects and to variables - Rimoldi, Horacio J. A. (2000)
The main purpose of this article is: given a score matrix called S, find out the joint proportional contribution of factors due to persons (conditions, situations, and so forth) and factors due to variables, for any sij observed score, where i identifies persons, and j, variables. This approach makes it possible a) to show that the same score in a given variable may have a different quantitative interpretation in terms of persons or conditions, and b) to find out how subjects differ in the way in which they relate variables.